Upaya Meningkatkan Kemampuan Berpikir Kritis Melalui Strategi Everyone is a Teacher Here - Muh Alif Kurniawan; Farida Nur Hikmah (Universitas Islam Sultan Agung, 2022)
The 2013 curriculum, Islamic religious education learning focuses on the student center, active students develop potential as optimally as possible, one of which is the ability to think critically as a provision in dealing with daily problems, but in PAI learning at Banguncipto State Elementary School students have not been able to think critically. The purpose of research is to develop critical thinking skills, including students issuing ideas that are in their minds, training students to improve their ability to exchange opinions objectively in order to find a truth. The research method used is Classroom Action Research. The results of the observations showed an increase in the ability of each student who seemed to be active in making questions, showed the ability to analyze to find information on the answers themselves, some students were right in making conclusions, which was related to critical thinking skills. The increase was also seen from the average result of the students' critical thinking ability test before the action only reached 54.86 with the less critical category. After taking action using the everyone is a teacher here strategy, the average test results reached 74.77 with a critical category.